New perspectives on the collective risk of extratropical cyclones - Hunter, Alasdair; Stephenson, David B.; Economou, Theodoros; Holland, Mark P.; Cook, Ian (Quarterly Journal of the Royal Meteorological Society, 2015)
© 2015 Royal Meteorological Society Author's final accepted version. The version of record was first published online 29 September 2015, before inclusion in an issue and is available from doi:10.1002/qj.2649 This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving In this study, the relationship between the frequency and intensity of extratropical cyclones over the North Atlantic is investigated. A cyclone track database of extended October-March winters was obtained from the National Centers for Environmental Prediction and National Center for Atmospheric Research (NCEP-NCAR) reanalysis. A large positive correlation is found between winter cyclone counts and local sample mean vorticity over the exit region of the North Atlantic storm track in this cyclone track database. Conversely, a negative correlation is found over the Gulf Stream. Possible causes for the dependence are investigated by regressing winter cyclone counts and local sample mean vorticity on teleconnection indices with Poisson and linear models. The indices for the Scandinavian pattern, North Atlantic Oscillation and East Atlantic Pattern are able to account for most of the observed positive correlation over the North Atlantic. To consider the implications of frequency intensity dependence for the insurance industry, an aggregate risk metric was used as a proxy for the annual aggregate insured loss. Here, the aggregate risk is defined as the sum of the intensities of all events occurring within a season. Assuming independence between the frequency and intensity results in large biases in the variance and the extremes of the aggregate risk, especially over Scandinavia. Therefore including frequency intensity dependence in extratropical cyclone loss models is necessary to model the risk of extreme losses. Natural Environment Research Council (NERC) Willis Research Network